METHODS OF EARLY DETECTION OF REJECTION IN A KIDNEY TRANSPLANT FROM A RELATIVE DONOR (Academicia Globe: Inderscience Research, 2021)
Kidney transplantation is considered to be the main method in the pathogenetic treatment of diseases associated with acute renal failure and other severe renal insufficiency, and this method is being improved day by day. In this regard, an electronic program has been developed to identify the elements of renal transplantation in place, in a timely manner, individually, and to predict the pre- or postoperative period, as well as early detection of rejection in transplantation.